2007
DOI: 10.7223/apjdm.1.91
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Causes of Dependency Under the Long Term Care Insurance Scheme in Japan

Abstract: After the introduction of the Long Term Care Insurance (LTCI), the number of persons who received the LTCI services increased very rapidly. This causes a rapid increase in LTCI expenditures and premium. In order to make LTCI scheme sustainable, it is pivotal how to maintain the ADL and health level of the elderly. For this purpose, we have investigated the causes of dependency among the LTCI users in order to establish an appropriate preventive strategy. The materials were LTCI related data (assessment sheet a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…On the contrary, oral function, nutrition score, depression score were not evaluated as significant risk factors. As our previous study indicated [1][2][3] , higher age category, male, bad mobility score, higher tendency to stay indoors (Tojikomori) and bad dementia score were detected as statistically significant risk factors in the current study. Various prevention activities have been organized based on these kinds of studies.…”
Section: Methodssupporting
confidence: 62%
“…On the contrary, oral function, nutrition score, depression score were not evaluated as significant risk factors. As our previous study indicated [1][2][3] , higher age category, male, bad mobility score, higher tendency to stay indoors (Tojikomori) and bad dementia score were detected as statistically significant risk factors in the current study. Various prevention activities have been organized based on these kinds of studies.…”
Section: Methodssupporting
confidence: 62%
“…For LTCI, the special program for maintenance and amelioration of ADL status has been introduced 5,6) . The slightly frail aged has to receive the preventive ADL services.…”
Section: ❖ Introductionmentioning
confidence: 99%
“…As our previous study indicated [5][6][7] , higher age category, male, bad mobility score, higher tendency to stay indoors (Tojikomori) and bad dementia score were detected as statistically significant risk factors of degradation of dependency level among the frail elderly. The official 25-items for case findings of frail elderly that is currently used, does not include age or health status.…”
Section: Discussionmentioning
confidence: 81%